Integrating Artificial Intelligence to Enhance Learning Motivation among Junior High School Students - Nugroho, Setyo; Haryanto, Sigit; Fuadi, Djalal (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to explore how the integration of Artificial Intelligence (AI) in classroom instruction enhances learning motivation among junior high school students. Although previous studies have shown that AI can support adaptive and engaging learning, most research has focused on higher education or fully online settings. Empirical evidence describing how AI influences student motivation in face-to-face junior high school classrooms in Indonesia remains limited. This study addresses that gap by examining students' and teachers' experiences using AI tools such as educational chatbots, learning analytics applications, and adaptive learning platforms.Methodology: A descriptive qualitative design was employed. Data were collected through classroom observations, in-depth interviews, and documentation analysis. Participants included students, teachers, and school administrators involved in AI-supported learning activities. The data were analyzed using thematic analysis to identify recurring patterns related to students' motivational changes and their interaction with AI tools during the learning process.Results: The findings show that AI integration enhances learning motivation in three key ways: (1) improving students' attention and interest through interactive and adaptive content; (2) increasing students' confidence via instant feedback and personalized guidance provided by AI systems; and (3) encouraging higher engagement through AI-based activities such as automated quizzes and digital simulations. Despite these benefits, challenges were also identified, including teacher readiness, limited availability of digital devices, and varied levels of students' digital literacy.Applications/Originality/Value: This study offers contextualized insights into how AI enhances learning motivation among junior high school students within Indonesian classrooms. It contributes to the limited body of qualitative research on AI in basic education, highlights practical considerations for effective AI integration, and provides valuable implications for future research on intelligent technologies in schools.